The maize premature senesence2 encodes for PHYTOCHROME‐DEPENDENT LATE‐FLOWERING and its expression modulation improves agronomic traits under abiotic stresses. (29th December 2020) - Gupta, Rajeev; Jiao, Shuping; Zhao, Suling; Meeley, Robert B.; Williams, Robert W.; Taramino, Graziana; Feng, Dongsheng; Li, Guofu; Liu, Juan; Allen, Stephen M.; Simcox, Kevin D.; Multani, Dilbag S.
Abstract: Among the various abiotic stresses, water and nitrogen are major stress factors that limit crop productivity worldwide. Since leaf nutrients remobilization during leaf senescence might impact response to abiotic stress in crops, we undertook a forward screen of the Mutator ‐active approach to identify premature senescence loci in maize. A mutant line isolated from a cross between a Pioneer Brand elite line and a public Mutator ‐active material, designated premature senescence2 ( pre2 ), expressed leaf senescence during flower initiation. The Pre2 gene encodes PHYTOCHROME‐DEPENDENT LATE‐FLOWERING (PHL) protein, a nuclear receptor coactivator. The pre2‐1 mutant allele was not a null mutation but produced a functional wild‐type transcript along with multiple mRNA species of varying lengths resulting from the alternate splicing of the Pre2 gene. The PHL accelerates flowering by suppressing the inhibitory effect of phyB on flowering in Arabidopsis (Endo et al., 2013). The ZmPRE2 polypeptide is highly conserved in plant species and has two identifiable motifs namely SPT20 and MED15. The Spt20 domain, which is a part of the SAGA (Spt‐Ada‐Gcn5 acetyltransferase) complex, is involved in histone deacetylation and MED15 proteins have nuclear functions in mediating DNA Pol II transcription. The differential spliced mature transcripts in both the pre2 alleles, as a result of transposon interference, were producing truncated proteins that lacked polyglutamine (Q) tract near the C‐terminus and might be causative of the premature senescence phenotype in maize. Endogenous gene suppression of ZmPre2 by RNAi improves maize agronomic performance under both water stress and suboptimal nitrogen conditions. The homozygous T‐DNA knockout of the pre2 homolog in Arabidopsis (At1G72390; the same insertional allele used by Endo et al., 2013) results in higher biomass, delayed maturity, enhanced tolerance to drought, and improved nitrogen utilization efficiency. The Arabidopsis mutant also showed hypersensitive response to 1 µM ABA (abscisic acid) concentration. These results indicate that the PHL protein plays a direct or indirect role in ABA‐dependent drought and N signaling pathways.